DEVELOPMENT PROSPECTS OF BEEF CATTLE BREEDING IN AND NON-TRANSMIGRATION AREAS - Wa Ode Suriani; Ferdinan C. Situmorang; A Rizal; Desmina Kristiani Hutabarat (Ikatan Dosen Menulis, 2023)
The research aims to determine the prospects of beef cattle breeding business development in transmigration and non-transmigration areas. The research method uses Stratified Sampling which stratifies 30 sub-districts which are transmigrant settlement areas, into three sub-district strata based on the cattle population. Data analysis was conducted in the form of data on respondent characteristics and maintenance management will be tabulated and analyzed into percentage values. Furthermore, the data is reviewed descriptively and SWOT analysis is carried out. Research on Beef Cattle business in Konawe Regency can be concluded: (1) Konawe Regency in general has good prospects and potential for the development of Beef Cattle supported by the availability of feed, seeds, business scale ≥ 4 heads reaching 84% and relatively easy livestock marketing. (2) However, the identified inhibiting factors are the land area of 78% of farmers only have ≤ 1 ha, the use of natural grass feed is still dominant (56%), livestock diseases are still dominantly untreated (62%), and the limited number of field extension workers.